Social capital building interventions and self-reported post-disaster recovery in Ofunato, Japan - Lee, Juheon; Aldrich, Daniel P.; Kiyota, Emi; Yasuhiro, Tanaka; Sawada, Yasuyuki (Scientific reports, 2022)
Evidence shows that communal resources, cohesion, and social infrastructure can mitigate shocks and enhance resilience. However, we know less about how specific social capital building interventions facilitate recovery in post-disaster environments. Using a survey of over 1000 residents of Ofunato, Japan after the 2011 Tohoku earthquake and tsunami, this study demonstrates that the individuals who actively participated in a community center—created for and led by neighborhood elders—reported higher levels of family and neighborhood recovery than similar individuals who did not participate. Results from ordinal logistic regression analyses, propensity score matching (PSM) and coarsened exact matching (CEM) show arguably stronger causal links between bottom-up, microlocal programs to boost connections in post-disaster areas and post-disaster outcomes. Community-based programs that strengthen social ties even among elderly residents can measurably improve their recoveries.